The natural products discovered in marine sponge-associated microorganisms: structures, activities, and mining strategy - Li, Peishan; Lu, Hongmei; Zhang, Yanzhu; Zhang, Xuejiao; Liu, Lianliang; Wang, Min; Liu, Liwei (Frontiers in Marine Science, 2023)
It is well known that microorganisms are abundant in sponges, which make up 50%-60% of the host biomass. Moreover, mounting evidence suggests that bacteria, fungi, and cyanobacteria, all associated with sponges, are the true creators of the bioactive compounds identified from sponges. The discovery of 774 structurally active compounds from 1998 to 2017 presents a good overview of natural product resources in sponge-associated microorganisms. During the last 5 years, many new molecules, including peptides, polyketides, alkaloids, and terpenes, have been identified from sponge-associated microorganisms through various mining strategies, exhibiting a wide range of biological activities, such as anti-microbial, anti-cancer, enzyme inhibition, and antioxidant properties. In this paper, 140 compounds produced by sponge-associated microorganisms from 2017 to 2022 are systematically discussed in terms of their structures, biological activities, and strain sources, as well as the mining strategies, which not only further updates the natural product library of sponge-associated microorganisms but also provides a new guideline for exploring the “dark matter” in sponges.